From ephemerality to delicacy: applying delicacy in the design space of digital gifting - Kwon, Hyosun (2017)
We encounter uncountable ephemeral phenomena in everyday life. Some of them are particularly appreciated for their ungraspable beauty and limited availability. From the outset, one strand of computing technology has evolved to encapsulate and preserve this transient experience. A myriad of digital devices has been developed to capture the fleeting moments and to store as digital files for later use, edit, share, and distribute. On the other hand, a portion of Human-Computer Interaction (HCI) research has engaged in adopting the transience of temporal phenomena in the design of interactive computing systems. Some computer and mobile applications metaphorically adopt the ephemerality in graphical elements or functions that resemble our real world experiences such as, forgetting and real-time conversation that naturally fades away immediately. Interactive artefacts or installations often incorporate ephemeral materials for abstract and artistic expression. Therefore, ephemeral artefacts or phenomena are often employed as a passive design element in ambient and peripheral interactions rather than in applications for practical purpose. However, ephemeral materials also engender experiences of a non-ambient nature. Some materials are physically fragile, only lasting for a brief moment, and therefore require constant care to retain their status, which might lead to highly focused attention, delicate interaction, and even a tense experience. This thesis aims to investigate how to harness the fleeting and irreversible feature of ephemeral artefacts in the design of practical products and services. This PhD builds on the methods of design-oriented HCI research. Thus, this thesis will present a research process that involves a series of challenges to initially frame a design problem in a fertile area for exploration; speculate a preferred situation; develop proof-of-concept prototypes to demonstrate the potential solution; and evaluate the prototypes through a user study. Contributions of this PhD have visualised by the outputs from multiple design studies. First, this thesis illustrates how the concept of ephemerality is currently understood in HCI. Then proposes a different approach to the use of ephemeral materials by shifting the focus to delicacy. The first design study introduces FugaciousFilm, a soap film based interactive touch display that shifted ephemerality from a user’s periphery to the focal point of interaction. The prototype is a platform for manifesting ephemeral interactions by inducing subtly delicate experiences. By demonstrating that ephemeral interactions reinforce user’s attention, delicacy was noticed as an attribute of user experience. By understanding of the use of delicacy, the research focus has moved from exploring how an individual ephemeral material can be utilised in interaction design, to harnessing delicacy of such materials in experience design that benefits Human-Computer Interaction. Thus, this thesis recaptures digital gift wrapping as a context by reviewing the current state of affairs in digital gifting in the field of HCI and design. A 5-stage gifting framework has been synthesised from the literature review and guided this PhD throughout the studies. The framework ought to be seen as a significant contribution in its own right. Based on this framework, a series of interviews was conducted to identify any weaknesses that reside in current media platforms, digital devices, and different modes of interaction. Hence, ‘unwrapping a digital gift’ has captured as a gap in the design space that could be reinforced by a delicate, ephemeral interaction. Therefore, this PhD proposes Hybrid Gift, a series of proof-of-concept prototypes that demonstrates digital gift wrappings. Hybrid Gift has been probed in a semi-structured design workshop to examine the use of delicacy and ephemerality in the design of digital gifting practices. The prototypes were designed to retrieve not only the unwrapping experience but also rituals around gift exchange. Therefore, this thesis discusses design implications of the findings that emerged throughout the study. Digital gifting is still an under-explored research area that is worthwhile to investigate through field works. Thus, the design implications and the framework are proposed to researchers and designers who wish to engage in the arena of digital gifting, also broadly in social user experience, and communication service and system design. From a macroscopic perspective, we are experiencing fleeting moments every second, minute, and day. However, they are rarely noticed unless we recognise that time passes irreversibly. This thesis extracted delicacy as a feature of ephemeral interactions and argued that it holds the potential to augment and enhance mundane experiences mediated by digital technology. In so doing, the series of design studies has conceptually influenced the design perspective to be shifted from material-oriented design to experience-focused design research. The design space of digital gifting would not have been recognised without the hands-on design practices in the process of this PhD. Finally, the proof-of-concept prototypes, framework, and design implications are thought to be of significance and value to the design students, researchers, and designers who want to employ similar methods and approaches in design research.